Tumor cell-derived secretory factor downregulates Semaphorin-3a in osteoblasts by activating mammalian target of rapamycin pathway. Issue 5 (3rd May 2016) - Yamada, Daisuke; Kawahara, Kohichi; Ozaki, Masanobu; Maeda, Takehiko
Abstract: We found that conditioned medium derived from Lewis Lung Carcinoma cells down-regulated Semaphorin3a ( Sema3a ) mRNA expression and increased the activity of mammalian target of rapamycin complex 1 (mTORC1) in osteoblast-like MC3T3-E1 cells. Furthermore, mTORC1 inhibition with rapamycin counteracted the effect of conditioned media on Sema3a mRNA expression. These results suggest that tumor cells decrease Sema3a mRNA expression in osteoblast in an mTORC1-dependent manner.